Aerobic fitness as a parameter of importance for labour loss in the heat. Issue 8 (August 2021) - Foster, Josh; Smallcombe, James W.; Hodder, Simon G.; Jay, Ollie; Flouris, Andreas D.; Morris, Nathan B.; Nybo, Lars; Havenith, George
Abstract: Objectives: To derive an empirical model for the impact of aerobic fitness (maximal oxygen consumption; V̇ O2max in mL∙kg −1 ∙min −1 ) on physical work capacity (PWC) in the heat. Design: Prospective, repeated measures. Methods: Total work completed during 1 h of treadmill walking at a fixed heart rate of 130 b∙min −1 was assessed in 19 young adult males across a variety of warm and hot climate types, characterised by wet-bulb globe temperatures (WBGT) ranging from 12 to 40 °C. For data presentation and obtaining initial parameter estimates for modelling, participants were grouped into low ( n  = 6, 74 trials), moderate ( n  = 8, 76 trials), and high ( n  = 5, 29 trials) fitness, with group mean V̇ O2max 42, 52, and 64 mL∙kg −1 ∙min −1, respectively. For the heated conditions (WBGT 18 to 40 °C), we calculated PWC% by expressing total energy expenditure (kJ above resting) in each trial relative to that achieved in a cool reference condition (WBGT = 12 °C = 100% PWC). Results: The relative reduction in energy expenditure (PWC%) caused by heat was significantly smaller by up to 16% for the fit participants compared to those with lower aerobic capacity. V̇ O2max also modulated the relationship between sweat rate and body temperature changes to increasing WBGT. Including individual V̇ O2max data in the PWC prediction model increased the predicting power by 4%. Conclusions: Incorporating individual V̇ O2max improved the predictive power of the heat stress index WBGT for Physical Work Capacity in the heat. The largest impact of V̇ O2max on PWC was observed at a WBGT between 25 and 35 °C.